Seed characterisation and micromorphology of taxa of the genus Crocus (Iridaceae) in Bulgarian flora - Tsvetanka Raycheva; Kiril Stoyanov (Historia naturalis bulgarica)
The morphology of seeds and SEM structure of epicuticular formations of the seed testa of 14 species of Crocus genus known so far for Bulgaria have been studied. The results have demonstrated great diversity. This study provided additional characteristics for the taxonomy of the crocuses that would be particularly useful for distinguishing some morphologically similar and critical species. A great diversity has been observed in the sculpturing pattern of the seed surface in the taxa studied. Discreet characters relevant to Crocus taxonomy have been revealed. The established differences in the microsurface structures correspond to differences in the metric and qualitative characteristics of the seeds in the studied taxa. Some of the investigated species of the genus Crocus in Bulgaria have been investigated for the first time by seed morphology. It follows from the obtained results that the morphological characteristics of the seeds are closely related to the taxonomy of the genus. As a result of the research, we proposed an analytical key for the recognition of the characteristics of the seeds.